Adults learning online: Digital choice and/or digital exclusion? - Eynon, R; Helsper, E (2011)
Using a nationally representative British survey, this article explores the extent to which adults are using the internet for learning activities because they choose to (digital choice) or because of (involuntary) digital exclusion. Key findings suggest that reasons for (dis)engagement with the internet or the uptake of different kinds of online learning opportunities are somewhat varied for different groups, but that both digital choice and exclusion play a role. Thus, it is important for policy initiatives to better understand these groups and treat them differently. Furthermore, the more informal the learning activity, the more factors that play a significant role in explaining uptake. Policies designed to support individuals' everyday interests, as opposed to more formal kinds of learning, are likely to be more effective in increasing people's productive engagement with online learning opportunities. © The Author(s) 2010.